Are Canned Beverages Industries Progressively Switching to Bisphenol AF?. Issue 11 (31st October 2019) - Russo, Giacomo; Varriale, Fabio; Barbato, Francesco; Grumetto, Lucia
Abstract: Seven bisphenols, endocrine‐disruptor chemicals, were analytically determined for risk assessment in 52 large‐consumption beverages collected from the Italian market. The analytes under examination were bisphenol A, bisphenol F, bisphenol E, bisphenol B, bisphenol AF, bisphenol A diglycidyl ether, and bisphenol M. The concentration levels of all bisphenols detected ranged from <LOQ to 1, 358 ng/mL in beers and from <LOQ to 76 ng/mL in energy drinks. The results of this monitoring study demonstrate the high presence of some congeners in beers, such as bisphenol AF, for which a European regulation is not yet available. Although the concentrations of the investigated bisphenols and that are under European regulations for migration into the food (Bisphenol A and BADGE) resulted below the legal limits in all screened beverages, the importance of their presence in foods should not be underestimated. Indeed, the safety of these analogues has not entirely been demonstrated and they could contribute to the total daily intake of endocrine disruptors, with special regards to specific demographics.